How Effective is Interfaith Dialogue as an Instrument for Bridging International Differences and Achieving Conflict Resolution? - Hunter, Shireen (The review of faith & international affairs, 2018)
The article asks the question of how effective interfaith dialogue is in resolving international conflicts. The answer the question, the article examines the question of how significant religion is in deciding the behavior of international state and non-state actors. Is it a key determinant of their behavior, or it is mostly an instrument to advance goals determined by other motives? It also the question whether religion is the main cause of international disputes. And if it is not a key determinant of behavior and main cause of disputes how can interfaith dialogues can help in resolving international disputes.